PENERAPAN JOINT VENTURE PADA PT. X - Muhamad Taufik (Jurnal Utilitas, 2021)
This research aims to find out the Application of Joint ventures in PT. X. This research uses qualitative methods that are qualitatively descriptive. For data sources selected purposive sampling with the criteria of mastering or understanding the application of a Joint Venture, the number of informants was as many as 3 people. Data collection techniques using non-participatory observation techniques, interviews, documentation studies, and triangulation. The results of the study showed that cooperation between capital owners was carried out both in terms of stock capital and also the formation of a board of directors and the composition of commissioners. The contractual/agreements used in this Joint Venture are the Joint Venture Agreement and articles of association. The advice in the implementation of this Joint Venture is that there needs to be a discussion from the board of directors or commissioners in order to achieve the goals well, and the need for more socialization for business activities that are being carried out, and socialization of work implementation to be in accordance with the regulations derived from either the Joint Venture Agreement or the Articles of Association.